HUBUNGAN KEBIASAAN OLAHRAGA DENGAN KEJADIAN DISMENORE PRIMER PADA REMAJA PUTRI - Yusdina Rizki Banurea; Arneliwati " "; Sri " Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Primary dysmenorrhea is one of the common problems experienced by most of the adolescent girls. Some factors that can prevent primary dysmenorrhea is  do good sporting habits with a frequency of 3 to 4 times a week with a duration of more than 30 minutes. The purpose of this study was to determine the relationship of exercise habits with primary dysmenorrhea among adolescent girls. Research Design is an analytic survey with retrospective approach.  This research was conducted in SMKN 7 Pekanbaru with 174 samples, taken by purposive sampling tehnique. Collection of data is done by giving a questionnaire. The analysis of data by using chi square test. The result of this research found that 21 respondents (12,1 %) had primary dysmenorrhea with regular exercise, and 153 respondents (87,9 %) had dysmenorrhea with irregular exercise habits.chi square test found p value 0,030 with alpha 0,05, so there is a significant correlation between exercise habits with primary dysmenorrhea in students SMKN 7 Pekanbaru. This research recommed to adolescent girls to increase their knowledge about dysmenorrhea and do regular exercise so that menstrual pain can be reduced.  Keywords: Adolescent girls, dysmenorrhea, habits sports